MR imaging and outcome in neonatal HIBD models are correlated with sex: the value of diffusion tensor MR imaging and diffusion kurtosis MR imaging - Bao, Jieaoxue; Zhang, Xiaoan; Zhao, Xin (Frontiers in Neuroscience, 2023)
Here, we aimed to determine the efficacy of diffusion kurtosis (DK) (mean kurtosis [MK]) and diffusion tensor (DT) (fractional anisotropy [FA], mean diffusion [MD], axial diffusion [AD], and radial diffusion [RD]) parameters for the early diagnosis of early brain histopathological changes and the prediction of neurodegenerative events in a full-term neonatal hypoxic-ischemic brain injury (HIBD) rat model. The HIBD model was generated in postnatal day 7 Sprague-Dawley rats to assess the changes in DK and DT parameters in 10 specific brain structural regions involving the grey matter, white matter, and limbic system during acute (12 h) and subacute (3 d and 5 d) phases after hypoxic ischemia (HI), which were validated against histology. Sensory and cognitive parameters were assessed by the open field, novel object recognition, elevated plus maze, and CatWalk tests.Repeated-measures ANOVA revealed that specific brain structures showed similar trends to the lesion, and the temporal pattern of MK was substantially more varied than DT parameters, particularly in the deep grey matter. The change rate of MK in the acute phase (12 h) was significantly higher than that of DT parameters. We noted a delayed pseudo-normalization for MK.Additionally, MD, AD, and RD showed more pronounced differences between males and females after HI compared to MK, which was confirmed in behavioral tests. HI females exhibited anxiolytic hyperactivity-like baseline behavior, while the memory ability of HI males was affected in the novel object recognition test. CatWalk assessments revealed chronic deficits in limb gait parameters, This is a provisional file, not the final typeset article particularly the left front paw and right hind paw, as well as poorer performance in HI males than HI females. Our results suggested that DK and DT parameters were complementary in the immature brain and provide great value in assessing early tissue microstructural changes and predicting longterm neurobehavioral deficits, highlighting their ability to detect both acute and long-term changes.Thus, the various diffusion coefficient parameters estimated by the DKI model are powerful tools for early HIBD diagnosis and prognosis assessment, thus providing an experimental and theoretical basis for clinical treatment.